Gamification and Tourism: the experience of built cultural heritage mediated by digital technology - Garcia, Ana P.; Frade, Davidson; Dias, Diego Roberto C.; Almeida, Marcela A. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
The way the world consumes culture has changed. Museums, cultural centers, and historical monuments have been transforming to adapt to these contemporary trends. Digital technology has been one of the allies in expanding the user experience in the cultural sphere, whether in virtual mode or places of visitation. The means of interacting with the user have taken on playful and participatory approaches to increase attractiveness and facilitate engagement, with gamification strategies standing out. This research aimed to understand how a playful experience, through a digital interface, can contribute to the leisure tourism experience while enhancing the historical and cultural heritage. To this end, a review of the literature was conducted to understand the characteristics and use of gamification in tourism and the development of a practical experiment, a gamified application for tourist visits to Matriz Nossa Senhora do Pilar church, a 18th-century Baroque church in the city of São João del-Rei, Minas Gerais.